2019
DOI: 10.2147/ott.s183944
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combining data from TCGA and GEO databases and reverse transcription quantitative PCR validation to identify gene prognostic markers in lung cancer</p>

Abstract: BackgroundThe aim of this study was to predict and explore the possible mechanism and clinical value of genetic markers in the development of lung cancer with a combined database to screen the prognostic genes of lung cancer.Materials and methodsCommon differential genes in two gene expression chips (GSE3268 and GSE10072 datasets) were investigated by collecting and calculating from Gene Expression Omnibus and The Cancer Genome Atlas databases using R language. Five markers of gene composition (ribonucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…It has also been demonstrated that CLIC3 is a glutathione-dependent oxidoreductase, and its function has a downstream reduction in transglutaminase-2 binding with its cofactor leading to a decrease in transglutaminase-2 activity, which is essential for physiologic function and regulation of extracellular stroma (Hernandez-Fernaud et al, 2017). Recently, CLIC3 was also proposed to be a prognostic marker for lung cancer (Liu et al, 2019).…”
Section: Clic3mentioning
confidence: 99%
“…It has also been demonstrated that CLIC3 is a glutathione-dependent oxidoreductase, and its function has a downstream reduction in transglutaminase-2 binding with its cofactor leading to a decrease in transglutaminase-2 activity, which is essential for physiologic function and regulation of extracellular stroma (Hernandez-Fernaud et al, 2017). Recently, CLIC3 was also proposed to be a prognostic marker for lung cancer (Liu et al, 2019).…”
Section: Clic3mentioning
confidence: 99%
“…In addition, the TRAF2 PF protective allele is associated with altered expression of at least five genes implicated in cell survival or death ( PHPT1, PTGDS, LCNL1, C8G, CLIC3 ). It is also associated with the expression of one gene related to size and inflammatory itching reaction, after mosquito bites ( AGPAT2 ) (6470). The AGPAT2 association is particularly interesting, given the epidemiological association of endemic PF with massive and continued exposure to mosquito bites (71, 72).…”
Section: Discussionmentioning
confidence: 99%
“…The world’s largest database of oncogene chips and integrated data-mining platform for cancer gene knowledge mining is currently the Oncomine database ( (Accessed on 25 January 2021)), with 86,733 pieces of cancer tissues and normal tissues and 715 gene expression datasets having been collected [ 70 , 71 ]. The classification of differential expressions of cancer types and their respective normal tissues were analyzed on the basis of the Oncomine database.…”
Section: Methodsmentioning
confidence: 99%